Towards a productive waqf management framework for socio-economic development of Muslim Community: a case study in Batam, Indonesia - Sanusi Patola Daeng Masirri, Sofiandi (2020)
This study aims to reconstruct and formulate the productive waqf management framework applicable to Indonesia. The objective is to improve productive waqf functions as an economic security net for the socio-economic development of the Muslim Community since they seemed to be subordinated in their homeland. This study has also been done as the answer towards some problems such as the low motivation and participation of Muslim in waqf, unprofessional nadzir, lack of waqf socialization and the roles of waqf that have been limited and forgotten by most Muslims. The study has been conducted on the Malay Community in Batam City since it has the largest number of population compared to other districts and 100% of the Malay people are Muslims. The study has also been done by involving two phases. The first phase was carried out with a quantitative approach by distributing 2 sets of the questionnaire. First, to 382 Malay people to analyze their level of awareness on the productive waqf. Second, to 156 samples of waqf managers (Nadzir) in Batam to analyze their level of participation in the productive waqf framework. The second phase was carried out qualitatively by using two rounds of Delphi techniques involving 14 waqf experts and documents analysis. This second phase was aimed to analyze the problems that arise in the current implementation of the productive waqf framework while obtaining important components along with their respective criteria. Finally, the proposed framework was verified by 7 experts in the expert opinion stage. The findings showed that (1) the level of awareness of Malay people living in Kampung Tua, Batam City is low. (2) Nadzir’s level of participation in the current productive waqf framework is medium. (3) There are 5 productive waqf framework components: supervision on waqf, nadzir aspect, legality, good modern management, shariahcompliant, and (4) the study has successfully come up with a new framework and component; merging Zakat, Infaq, and Shadaqah with Waqf Boards for developing socio-economic life of the Muslim community in Indonesia.